Evaluation of broiler meat in experimental listeriosis - Borovuk, Iryna; Zazharska, Nadiia (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The work aimed to assess the safety and quality of broiler meat in experimental listeriosis changes in storage. Materials and Methods: Ross Cobb 500 chickens (40) were divided into 4 groups of 10 animals each. Chickens from three experimental groups were infected by Listeria innocua, Listeria ivanovii, and Listeria monocytogenes. Meat samples were stored for 5 days at 0°C–4°C. Meat samples were kept in the refrigerator for 3, 4, and 5 days. Microbiological and laboratory indicators of meat freshness were found on these days as well. Results: After the slaughter of chickens with experimental listeriosis, pathological changes in muscles and organs were noted against the background of fattening carcasses with a high slaughter yield. By bacterial contamination, 1 day after slaughter, the meat of chickens of the experimental groups (L. innocua, L. ivanovii, and L. monocytogenes) outperformed the control group by almost 1.9, 13.9, and 24.7 times, respectively (p < 0.05). The same trend is observed for the third, fourth, and fifth days of meat storage. To keep chicken meat fresh for 5 days, only samples from the control group stayed fresh. Conclusion: According to the total bacterial contamination, the meat of chickens of the groups L. innocua and L. ivanovii was dangerous to human health after 5 and 4 days of storage, respectively. From the first day after the chickens were killed, the meat of chickens that had been infected with L. monocytogenes did not meet the requirements (up to 100 CFU/gm) and was not safe to store or eat. J. Adv. Vet. Anim. Res., 9(1): 155–165, March 2022 http://doi.org/10.5455/javar.2022.i580